把分式(x^2+x-3)/((x-1)(x-2)(x-3))写成A/(x-1)+B/(x-2)+C/(x-3)的形式.

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/03 22:47:02
把分式(x^2+x-3)/((x-1)(x-2)(x-3))写成A/(x-1)+B/(x-2)+C/(x-3)的形式.

把分式(x^2+x-3)/((x-1)(x-2)(x-3))写成A/(x-1)+B/(x-2)+C/(x-3)的形式.
把分式(x^2+x-3)/((x-1)(x-2)(x-3))写成A/(x-1)+B/(x-2)+C/(x-3)的形式.

把分式(x^2+x-3)/((x-1)(x-2)(x-3))写成A/(x-1)+B/(x-2)+C/(x-3)的形式.
我不容易呀、、、用了20分钟……
依据“1/a+1/b+1/c=(bc+ac+ab)/abc”,
所以,x^2+x-3相当于(x-2)(x-3)a+(x-1)(x-3)b+(x-1)(x-2)c
则,(x^2-5x+6)a+(x^2-4x+3)b+(x^2-3x+2)c=x^2+x-3
最后实验,得:a=-1/2,b=-3 ,c=9/2 .
所以,(x^2+x-3)/((x-1)(x-2)(x-3))
=(-1/2)/(x-1)+(-3)/(x-2)+(9/2)/(x-3)